Morphological features of Late Ordovician (Sandbian) bryozoans from the basin of Khrevitsa River (north-western Russia) and description of a new species of the genus Prophyllodictya Gorjunova, 1987 - Tolokonnikova, Zoya A.; Fedorov, Petr V. (Zootaxa, 2023)
Some Sandbian (Late Ordovician) bryozoans are here described from the Leningrad region, north-western Russia. The studied association is represented by eight species including one new cryptostome bryozoan Prophyllodictya khrevitsa n. sp. We explore the colony morphology and evolutionary morphogenesis of Prophyllodictya Gorjunova, 1987 and discuss the morphological features of trepostome and cryptostome bryozoans from the Khrevitsa Formation. Finally, we classify protective structures in bryozoan colonies in three groups based on functional criteria: 1) structures to strengthen the colony, 2) structures to defend the colony against predators, and 3) structures to protect the polypide.